Evaluating the risk of osteopenia-related adverse events with antiepileptic drugs: a pharmacovigilance study based on the FAERS database - Yang, Nan; Han, Xiang; Hua, Hongning; Wang, Yumeng; Chen, Yulin; Zhou, Yue; Feng, Haoyu (Frontiers in Pharmacology, 2025)
BackgroundControversy remains regarding the association between antiepileptic drugs and osteopenia, and this study aims to investigate and address this gap using real-world data.Materials and methodsThis study included data from the United States (U.S.) Food and Drug Administration Adverse Event Reporting System (FAERS) from the first quarter of 2005 to the first quarter of 2025. A disproportionate analysis method and Bonferroni-corrected p-value were used to detect association signals between antiepileptic drugs and osteopenia. Additionally, subgroup analyses were conducted to explore differences among different age and gender groups.ResultsAmong the 206,680 adverse events associated with 12 commonly used antiepileptic drugs recorded in the FAERS database during the study period, 181 were attributable to osteopenia. Positive drug safety signals were detected for phenytoin, valproic acid, gabapentin, and eslicarbazepine.ConclusionPrevious studies have only identified a link between phenytoin and osteopenia, while the relationship between valproic acid and this adverse event remains controversial, and gabapentin and eslicarbazepine have not been systematically reported. The findings provide the first evidence of an association between these four antiepileptic drugs and osteopenia, offering insights and guidance for clinical recognition and prevention of such events.